CONTENT OF DEVELOPMENT OF REFLECTIVE COMPETENCE OF FUTURE PRIMARY CLASS TEACHERS ON THE BASE OF INTEGRATIVE LESSONS (CAHIERS MAGELLANES-NS, 2024)
In the world, special attention is paid to the development of a modern approach to the formation of professional competence of future teachers, to the improvement of the pedagogical mechanisms of creating an integrative educational environment. At the same time, on the basis of the formation of an integrative approach to the teaching of subjects, priority is given to the improvement of social-pedagogical mechanisms of ensuring that the educational process of schools is brought to a higher level [1]. In particular, in the process of expanding the scientific outlook of future primary school teachers and improving the quality of their knowledge, a wide application of the integrative approach to the content of pedagogical education, as well as an effective method of educating future primary school teachers The development of a training system is gaining importance.